Impact of counseling on cervical cancer and its screening on women knowledge, health beliefs and protective practices - HosseAbedelAzim Mohamedin, Hoda; El-sayed Hossein, Yosria (International Journal of Advanced Nursing Studies, 2018)
Background: Cervical cancer can be preventable or detected early especially with a series of regular screening with Pap tests.Aim of the study: The aim of this study were to evaluate the impact of counseling on cervical cancer and its screening on women knowledge, health beliefs and protective practices.Subjects and Methods: A quasi-experimental design was used. A convenient ample of 120 women were randomly divided into experimental and control groups, each group consisted of 60 women were recruited from outpatient clinic at Obstetrics and Gynecology Department at Minia General Hospital.Results It can be observed that, 86% of the women in the intervention group had good knowledge compared to only 17% of the control group and the difference is statistically significant. The mean score of perceived susceptibility and barriers in both groups was reduced but the decrease was significantly higher in the intervention group (P<0.004). The mean score of perceived severity and benefits in both groups were increased, but the increased mean score in the intervention group was higher. A highly statistical significant difference was observed between groups regarding protective practices (p = .001).Conclusion: It can be concluded that there was a highly statistical significant improvement in women knowledge was observed and the higher positive beliefs about perceived benefits of preventive health practices, susceptibility, severity, health motivation and reduced the barriers of pap smear this can influence womenâ€™s willingness to take preventive test and higher participation in regular Pap smear test in the intervention group. The most commonly barriers to screening cited in our study are lack of knowledge.Recommendations: on the light of this findings it is recommended that, women should be encouraged to take responsibility for their own health and be active participants in the screening program, More educational intervention is needed to encourage adherence to routine cancer screening with raising womenâ€™s awareness about cervical cancer, The barriers to Pap smear test are considered by the health authorities in order to overcome barriers of cervical cancer screening.Â Â